Laboratory Assessment of Patients with Suspected Rheumatic Musculoskeletal Diseases: Challenges and Pitfalls - Carubbi, Francesco; Alunno, Alessia; Cipriani, Paola; Bistoni, Onelia; Scipioni, Rosa; Liakouli, Valiki; Ruscitti, Piero; Berardicurti, Onorina; Di Bartolomeo, Salvatore; Gerli, Roberto; Giacomelli, Roberto (Current Rheumatology Reviews, 2019)
Current patient care in rheumatology relies primarily on a combination of traditional clinical assessment and standard laboratory tests. Investigators seek to discover new biomarkers and novel technologies to boost the research in this field. Mechanistic biomarkers such as cytokines, cell types, antibodies, signaling molecules, are rooted in the mechanism underlying the disease and can guide the clinical management of the disease. Conversely, descriptive biomarkers are byproducts of the disease process, depict the state of a disease but are not involved in its pathogenesis. In this article, we reviewed the field of common laboratory biomarkers in rheumatology, highlighting both their descriptive or mechanistic value as well as their role in clinical practice.
Keywords: Laboratory